How User Personality and Social Value Orientation Influence Avatar Mediated Friendship - Chesney, T.; Chuah, S.; Hoffmann, R.; Hui, Wendy; Larner, J. (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to study the influence of user personality and vlaues on the number of connections users make, the number of requests for connections that users give out, and the number of connections invitations users receive. Design/methodology/approach – This is a field study of 179 participants interacting in a novel virtual world. The world’s server logs are used to capture sociometrics about the users and their interaction. Findings – Findings suggest that personality and values influence the number of friends users make and the number of friendship requests users give out, but not the number of friendship invitations users receive. Only one personality trait – conscientiousness – exhibits homophily. Originality/value – Personality and social value orientation have rarely been studied together in information systems (IS) research, despite research showing the two have an impact on IS relevant constructs. The use of server logs for data capture is novel. Avatar friendship is an under-researched concept in IS.